Neonatal meningitis in a full-term neonate due to Streptococcus mitis oralis: a case report - Sonia Kapoor; Carlos Daniel Varela Chinchilla; Eric J. Stern (BMC Pediatrics)
Abstract Background The incidence of neonatal sepsis in the United States of America is 1–2 cases per 1,000 live births. The majority are bacterial infections due to Escherichia coli and Group B Streptococcus. Only a few reported cases due to Streptococcus mitis oralis exist in the literature with limited information regarding management and treatment. Case presentation We report a case of Streptococcus mitis oralis bacteremia and meningitis in a full-term 38 week and 6-day-old female neonate born to a 37-year-old G2P2 mother initially treated with ampicillin and gentamicin for presumed Group B Streptococcus (GBS) sepsis and meningitis, then completing a 14-day treatment course with cefepime. Conclusion Clinicians should be aware of S. mitis oralis as it can cause significant illness in both pre-term and term neonates, a population more susceptible to infection. Due to the low incidence of cases, there are no specific guidelines for management of Streptococcus mitis sepsis or meningitis in the newborn. We highlight our clinical decision-making regarding antibiotic selection and treatment duration while focusing on enhancing treatment efficacy based on antimicrobial susceptibilities.